Novel Virus-Like Particle Vaccine Encoding the Circumsporozoite Protein of Plasmodium falciparum Is Immunogenic and Induces Functional Antibody Responses in Mice - Kurtovic, Liriye; Wetzel, David; Reiling, Linda; Drew, Damien R.; Palmer, Catherine; Kouskousis, Betty; Hanssen, Eric; Wines, Bruce D.; Hogarth, P. Mark; Suckow, Manfred; Jenzelewski, Volker; Piontek, Michael; et al. (Frontiers in Immunology, 2021)
RTS,S is the leading malaria vaccine in development, but has demonstrated only moderate protective efficacy in clinical trials. RTS,S is a virus-like particle (VLP) that uses the human hepatitis B virus as scaffold to display the malaria sporozoite antigen, circumsporozoite protein (CSP). Particle formation requires four-fold excess scaffold antigen, and as a result, CSP represents only a small portion of the final vaccine construct. Alternative VLP or nanoparticle platforms that reduce the amount of scaffold antigen and increase the amount of the target CSP antigen present in particles may enhance vaccine immunogenicity and efficacy. Here, we describe the production and characterization of a novel VLP that uses the small surface antigen (dS) of duck hepatitis B virus to display CSP. The CSP-dS fusion protein successfully formed VLPs without the need for excess scaffold antigen, and thus CSP represented a larger portion of the vaccine construct. CSP-dS formed large particles approximately 31-74 nm in size and were confirmed to display CSP on the surface. CSP-dS VLPs were highly immunogenic in mice and induced antibodies to multiple regions of CSP, even when administered at a lower vaccine dosage. Vaccine-induced antibodies demonstrated relevant functional activities, including Fc-dependent interactions with complement and Fcγ-receptors, previously identified as important in malaria immunity. Further, vaccine-induced antibodies had similar properties (epitope-specificity and avidity) to monoclonal antibodies that are protective in mouse models. Our novel platform to produce VLPs without excess scaffold protein has wide implications for the future development of vaccines for malaria and other infectious diseases.